Aircraft tires : key principles for landing gear design - Schmidt, R. Kyle (SAE International, 2022)
Landing gear provides an intriguing and compelling challenge, combining many fields of science and engineering. Designed to guide the interested reader through aircraft tire design, selection, and integration to the aircraft landing gear, this book presents a specific element of landing gear design in an accessible way. The author's two volume treatise, The Design of Aircraft Landing, was the inspiration for this book. The Design of Aircraft Landing is a landmark work for the industry and utilizes over 1,000 pages to present a complete, in-depth study of each component that must considered when designing an aircraft's landing gear. While recognizing that not everyone may need the entire treatise, Aircraft Tires: Key Principles for Landing Gear Design is one of three quick reference guides focusing on one key element of aircraft design and landing gear design. This volume features tire construction and terminology, mechanics of pneumatic tires, tire performance and modeling as well reviewing undesirable tire behavior. R. Kyle Schmidt has over 25 years' experience across three countries and has held a variety of variety of engineering roles relating to the development of new landing gears and the sustainment of existing landing gears in service.